Some aspects need to be considered in assessment and treatment of sarcopenia - Erdogan T (Dove Medical Press, 2018)
Tugba Erdogan, Gulistan Bahat Department of Internal Medicine, Division of Geriatrics, Istanbul University, Istanbul Medical School, Istanbul, TurkeyWe have read the review article by Ilaria Liguori et al1 with great interest. In this article, authors aimed to review sarcopenia in terms of assessment of its burden and strategies to improve outcomes. We have some comments that would contribute on this extensive review. Authors reported that the diagnosis of sarcopenia requires the presence of both low muscle mass and low muscle function. Authors defined low muscle function as gait speed lower than 0.8 m/s and/or a grip strength lower than 26–30 kg for men and 16–20 kg for women. However, it should be noted that European Working Group on Sarcopenia in Older People (EWGSOP) recommends use of normative data of the study population for muscle mass and muscle strength cutoff points. After EWGSOP publication, population-specific cutoff values, including the Turkish and Korean population, have been published and better to be included in a paper aimed to review sarcopenia in this context.2View the original paper by Liguori and colleagues.